Vegetation analysis in colonies of an endangered rodent, the Cabrera vole (Microtus cabrerae), in southern Portugal - Santos, Sara M. (2009)
The Cabrera vole (Microtus cabrerae) is a threatened rodent endemic in the Iberian Peninsula with a patchy distribution and specific microhabitat requirements. This aim of this study was to document the composition of plant communities in habitats of Cabrera vole colonies in southern Portugal. Differences observed in plant species composition were also compared with vegetation structure, taxonomic and life form groups, species and group diversity, disturbance,topography and soil properties. Vegetation was sampled between March and July 2004, in 26 colonies occurring in five geographical areas. Grasses were the most abundant, common and diverse family in the colonies, and the perennial grass Agrostis castellana was present in 92% of colonies, with a mean cover of 16% of the site. Other frequently occurring species were Briza maxima (85%), Vulpia myuros (85%), Gaudinia fragilis (81%), Leontodon spp. (81%), Avena barbata (77%), Bromus hordeaceus (77%) and Tolpis barbata (77%). Colonies were classified in eight vegetation groups that included meadows, tall perennial grasslands, manured meadows with tall sedges, annual grasslands and ruderal and nitrophilous grasslands. Main gradients associated with composition differences were grass richness, annual and perennial grass cover, vegetation structure (herbaceous vegetation height), soil properties (texture and moisture), disturbance (ruderal species) and colony dimensions (area). Results suggest that the Cabrera vole is able to exploit a wide variety of grasslands, with a varying degree of ecological disturbance. Meadows and perennial grassland communities seem to be higher quality microhabitats for voles.